Análise espacial da conectividade estrutural na paisagem: uma aplicação no Mosaico de áreas protegidas do Espinhaço: Alto Jequitinhonha Serra do Cabral - Rodrigo Pinheiro Ribas (2015)
In different parts of the globe, pressure on the use of natural resources has been in excessive scope and has caused loss of connectivity among natural habitats in the landscape, creating in this way fragmented areas with less environmental regulations. Preservation of natural areas is the most primary form biological diversity conservation. However, oftentimes these protected areas are created or can become isolated fragments in areas that have already succumbed to anthropic pressure, being the integrated management of protected areas necessary. The methodological approach of this study was done within a unit that directs its actions towards an integrated management of protected areas inside its limits. This unit is the Mosaic of Protected of the Espinhaço: Alto Jequitinhonha - Serra do Cabral. The main objective of this thesis is to present a methodological proposal of analyzing structural connectivity in the landscape in the study region. It uses as theoretical and technical support the concepts inherent to Geoprocessing and Landscape Ecology. Justification for carrying out this thesis is the possibility of observing processes that may be harmful to maintenance of biodiversity and as a contribution to the planning and management of areas that need to protect natural resources. The results indicate paths for the creation of legal instruments and management models that work in an integrated form. The thesis was developed sequentially in the preparation of five articles. This presentation format proved to be more interesting due to this works methodological dynamic that is interconnected, being that when a step is previously concluded, it offers subsidies to carry out the step to be done a posteriori.